The Development of Articulation Learning Model Oriented to Student Activity in Economic Subjects at Pekanbaru Plus Binabangsa High School - Silvi, Sinta Ramadhan; Suarman, Suarman; Kartikowati, Rr Sri (Journal of Educational Sciences, 2019)
Not all students have the ability to speak or to express opinions in public well, and not all students are able to engage in the learning process with a student centered approach. Therefore, the learning model with a student centered approach should still be juxtaposed with the considered percentage of lecture method (teacher cantered approach). This research aims to produce an Articulation learning model development oriented towards student activities. The data analysis was referring to the ISMAN model which consists of the stages: input, process, output, feedback, and learning. Based on the validity test to the validator, the Articulation development model is declared suitable for the Economics learning process. The students responses to the utilization of the Articulation development model obtained an average percentage of 88.62% in the category of very effective.